On the movement behaviour of elite swimmers during the entry phase - Fischer, S.; Kibele, A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
For years, allusions to the particular importance of the entry and underwater phase for the swim start have been a topic of interest in the swimming literature (Guimaraes & Hay 1985; Bonnar 2001; Cossor & Mason 2001; Vilas-Boas et al. 2003). Based on Guimaraes and Hay (1985) the movement phases during the swim start can be structured by the block-, flight-, and water-phase. Maglischo (2003) additionally subdivided the water-phase into the entry, gliding, and emersion-phase. Guimaraes and Hay (1985) point out that 95% of the variance in the performance of the start can be explained by differences in the gliding phase (consisting of entry, gliding and emersion phase). In this regard, the gliding phase and the emersion phase have been investigated by several authors (Lyttle et al. 1999; Pereira et al. 2006; Elipot et al. 2009; Marinho et al. 2009; Elipot et al. 2010; Vantorre et al. 2010). In addition, there are various studies exhibiting that differences between starting techniques during the take-off phase do not necessarily result in different swim start times (Mclean et al. 2000; Vilas-Boas et al. 2003; Welcher et al. 2008; Vint et al. 2009; Biel et al. 2010). In these studies, none of the variables representing the take-off on the block, the flight phase, or the gliding phase could account completely for the variance found in the swim start times. Based on these findings, the special importance of the entry phase was derived. Similarly, Sanders and Byatt-Smith (2001) and Sanders and Bonnar (2004) argue that, concerning the overall start performance, a greater emphasis should be given to the entry phase when compared to the take-off phase. Remarkably, so far, no study has addressed the issue of the optimal movement behavior during the entry phase. However, speculations have been published on whether the pike or the flat dive would be more beneficial to the swim start performance (Maglischo 2003). For the entry phase, several variables have been investigated. These variables relate to the entry angle (Holthe & Mclean 2001;. Vilas-Boas et al. 2003; Miller et al. 2003; Gu, Tsai & Huang 2003; Kibele & Fischer 2009), the hip-angle at water entry (Kibele et al. 2007; Kibele & Fischer 2009), and the angle of attack (Gu et al. 2003). Studies that ascribe benefits to the flat dive (Counsilman et al. 1988; Kirner et al. 1989) contrast other studies showing advantages for a pike dive (Mills & Gehlsen 1996). Other studies did not find any differences between the two entry variants (Hobbie 1980; Holthe & Mclean 2001; Gu et al. 2003; Fischer & Kibele 2009). Due to the different methodological approaches used to assess the entry angle the studies published on the entry behavior cannot be properly compared (Guimaraes & Hay 1985; Gu et al. 2003; Miller et al. 2003; Kibele et al. 2007; Fischer & Kibele 2009). In addition to differences between methodological approaches, kinematic parameters representing the entry behavior are difficult to assess as air particles are swept along the body surface distorting visibility in the video analysis. Until recently, this problem remained unresolved. However, using a now analysis tool'algorithm for the determination of body segment coordinates under blurred visual conditions' the kinematic data of the movement behavior during entry can be analyzed (Kibele & Fischer 2009; Fischer 2013) The objectives of this study were (a) to derive key parameters for the analysis of the entry phase and (b) to identify different movement strategies for the entry phase based on these parameters. We hypothesised that, in addition to the previously known strategies for the entry behavior ('pike vs.flat'), further movement possibilities exist.